Which user errors matter during HIV self-testing? A qualitative participant observation study of men who have sex with men (MSM) in China - Chongyi Wei; Li Yan; Jianjun Li; Xiaoyou Su; Sheri Lippman; Hongjing Yan (BMC, 2018)
Abstract Background The World Health Organization recommends HIV self-testing (HIVST) as an additional approach to HIV testing services. We aimed to assess to what extent HIVST was conducted correctly by Chinese men who have sex with men (MSM) and to identify user errors during the HIVST process in order to inform strategies to optimize its use and thus reduce the number of undiagnosed HIV infections. Methods Between February and March 2017, participant observations were conducted with 27 MSM in an east coastal city in China. In the presence, but without the assistance or orientation, of a trained HIV testing counselor, participants conducted HIVST (either finger prick or oral fluid) according to manufacturers' instructions. Errors were recorded on checklists during direct observation and double checked afterwards by reviewing video files of the observations. Results Overall, 12 participants (44.4%) had invalid test results due to user errors. Just five (18.5%) did not make any errors during the entire HIVST process. Failure to follow all the steps based on manufactures' instructions was a common problem for both finger prick and oral fluid self-testers. For finger prick users, most errors occurred during the stage of collecting the specimen. In contrast, oral fluid users made most errors during the stage of testing the collected specimen. Conclusions Although we found that user errors were common among MSM administering HIVST, this should not deter or discourage routine implementation and scale-up of HIVST as strategies can be implemented to facilitate the correct use of HIVST. Trial registration This study was a part of a clinical trial: ClinicalTrials.gov (#NCT02999243); Registration date: December 20, 2016.